Penerapan Restorative Justice dalam Penegakan Hukum Kasus Investasi Ilegal di Indonesia: Implementation of Restorative Justice in Law Enforcement of Illegal Investment Cases in Indonesia - Syahruddin, Nurul Insi; Topo Santoso; Desi Fitriyani; Winda Sari (Jurnal Ilmiah Penegakan Hukum, 2025)
When discussing illegal investment cases, of course some investors are victims. This paper is motivated by the pros and cons related to the application of the concept of restorative justice in law enforcement of illegal investment cases in Indonesia. This paper will examine the arrangements and efforts of law enforcement officials and the application of restorative justice in law enforcement of illegal investment cases in Indonesia. The method used is normative legal research. Regulations relating to illegal investment are regulated in Law Number 10 of 1998, Law Number 25 of 2007, and Decree of OJK Board of Commissioners Number KEP-72/D.04/2021. The authorised institution in the financial sector, in this case OJK through SWI, does not have the authority to follow up on illegal investment cases apart from blocking the site/website/application so that it only submits information reports to the Police Criminal Investigation Unit. In preventing and prosecuting rounds of companies that invest illegally, OJK has a preventive and repressive role regulated in the OJK Law. Meanwhile, restorative justice can be applied in the prosecution of illegal investment cases in Indonesia, taking into account the applicable legal instruments, objectives, and related constraints. However, its application requires the consent of the victim. The application of restorative justice in the prosecution of illegal investment cases requires optimal efforts in tracing the perpetrators, both the main perpetrators and other actors involved, through coordination between the Investment Alert Task Force and the National Cyber Agency to prevent other parties from reopening illegal investment offers. If the case proceeds to the court or prosecution stage, restitution can be made by involving the Witness and Victim Protection Agency.